Statistical analysis on tribology behavior of stainless steel surface in aloe vera blended lubricant. Issue 5 (January 2020) - Amirruddin, A K; Kadirgama, K; Ramasamy, D; Rahman, M M
Abstract: Lubricant oil is one of the important oils that is needed for any vehicle and the additive added into the lubricant is required to boost the potential of lubricant to protect engine or any compartment that required lubrication. The presence of lubrication oil is very important in engine which is functioned to protect engine especially during combustion processes and it is needed to cool down the temperature of engine after every process. However, most of the lubricant oils are not very eco-friendly and they can have caused harm to the environment system. Several researches have been carried out recently to find new alternative additives for lubricant oil and it is safer for our environment which is now in danger. One of the alternative additives that have been widely suggested by several researchers is involving plant such as vegetables. An experiment has been carried out to justify the potential of Aloe Vera as a new additive that can replace existence chemical and synthetic additive which is harmful to the environment and costly to produce it. The conclusion of the experiments is the researcher agrees to the suitability of Aloe Vera as a new additive by using simple experiments method. Response surface method was used to design the experiments and finding the relationship between the parameters and responses. It shows that Aloe Vera additives reduce the coefficient of friction.